Evaluating implementation supports delivered within problem-solving consultation. (February 2019) - Collier-Meek, Melissa A.; Sanetti, Lisa M.H.; Levin, Joel R.; Kratochwill, Thomas R.; Boyle, Ashley M.
Abstract: Teachers participating in problem-solving consultation often struggle to maintain adequate treatment fidelity, which is necessary to improve student outcomes. Low levels of treatment fidelity may result from implementation barriers, such as intervention compatibility, implementer skill, and implementer motivation. This study involves the evaluation of five implementation supports designed to address implementation barriers (i.e., Implementation Planning, Role Play, Participant Modeling, Raising Awareness, Motivational Consulting) within problem-solving consultation. Across 14 randomized individual single-case AB intervention designs, we evaluated the impact of these implementation supports on teacher treatment fidelity of classroom management plans and class-wide academic engagement and disruptive behavior. Visual analysis, descriptive statistics, and randomization test analyses suggest that these implementation supports have the potential to be broadly effective in improving teachers' fidelity and student outcomes. Teachers required a different number of supports to increase fidelity levels and rated the implementation supports positively. Implications of the study's findings are described.